Eighteenth century economics : Turgot, Beccaria and Smith and their contemporaries - Groenewegen, Peter D. (London ; New York : Routledge, 2002)
This book is a comparison to illuminate the origins of classical political economy and to delineate its major characteristics,economy in the eighteenth century.
Includes bibliographical references and index.
nmn, 01/08/19
Loans
Keywords: Smith, Adam; Turgot, Anne-Robert-Jacques; Quesnay, François; Economics; Free trade; Physiocrats